KEABSAHAN SAKSI DALAM PERNIKAHAN MENURUT HUKUM ISLAM - Hafidhul Umami; Qurratul Aini (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
A marriage witness is a person who sees, hears, or knows about an event/occurrence of a marriage contract between the marriage guardian/representative and the prospective husband/representative with the aim that they will be able to provide the necessary information in the interest of the marriage case that they know about. The presence of witnesses in a marriage contract is a determinant of whether or not the marriage contract is valid. The legal basis for witnesses in marriage consists of the Al-Qur'an and Hadith. Certain conditions that can be appointed as a witness in the marriage contract are a Muslim man, fair, aqil, mature, not impaired memory and not deaf or deaf (Article 25 KHI).